Synthesis and biological evaluation of new pyrimidine-4-yl-ethanol derivatives as ROS1 kinase inhibitors - Abdelazem, Ahmed Z.; Lee, So Ha (INFORMA HEALTHCARE, 2015)
As a part of trials to target ROS1 kinase with potential inhibitors, a novel series of pyrimidin-4-ylethanol and ethanone derivatives (4a-f, 5a-f, 6a-f and 7a-f) have been designed based on previously discovered lead compounds KIST301072 and KIST301080, and synthesized on 4-5 steps according to compounds. The structures of the newly synthesized compounds have been confirmed on H-1-NMR, C-13-NMR and IR. Most of the tested compounds showed ROS1 kinase inhibitory activity in micromolar range.
Keywords: PROTEIN-KINASES; CANCER; TARGETS